The effects of an increase in female legislators on government expenditures in sectors identified as "for women" - Villamor, Jose Miguel S. (School of Economics, University of the Philippines Diliman, 2018)
In light of the Sustainable Development Goals of 2030, researchers recognise the value of pushing for Goal 5_ Gender equality and women_s empowerment in advancing towards a more progressive society. Previous literature has found a positive relationship between female representation and female labor force participation. Using cross_country time_series analysis, researchers investigate the effects of an increase in female political participation in the legislature on government expenditure for sectors that are identified as _for women_, particularly in education, health, and social welfare. The data covers 4 South_East Asian countries from 2000_2017. This thesis distinguishes itself among previous works on the study by utilizing the Seemingly Unrelated Regressions model, owing to the condition that equations are linked by their error terms being contemporaneously correlated. The study finds a positive correlation between the number of females in national parliaments and government expenditure levels in both education and social welfare departments or ministries. Researchers have also noted that the largest coefficients are linked with country and time dummy variables. This suggests that factors unique to each country have a more visible effect on expenditure over the variables observed.